Hybrid Investigative Journalism - Konow-Lund, Maria; Park, Michelle; Bebawi, Saba (Springer Nature, 2024)
This open access book is a rare example of the ethnographic study of investigative journalism. This book explores entrepreneurial attempts to combine traditional investigative journalism with alternative ways of organising this work. It transcends watershed investigative projects in favour of the ways in which new actors (citizens, technologists, bloggers and local reporters, among others) join experienced investigative journalists in experiments with the practices of watchdog journalism in the digital era. Cases include Bristol Cable, Bureau Local and the Korea Center for Investigative Journalism, as well as Forbidden Stories. The book also includes two chapters on the impact of COVID-19 upon the development of cross-disciplinary work in a traditional newsroom and in the larger media ecosystems of both Norway and China. This is a timely book for journalism students, scholars and investigative reporters, who share a passion for this form of journalism.